An analysis of speech errors of English for Occupational Purposes (EOP) learners at the International Islamic University Malaysia (IIUM) - Ahamad Shah, Mohamed Ismail; Abd. Karim, Norfazlika (© IDOSI Publications, 2014, 2014)
Abstract: This study examined errors made in grammar in the speech transcripts of 15 EOP learners. The errors were divided into 9 sub-categories: wrong use of nouns, countable use of uncountable nouns, nouns used as verbs, wrong use of prepositions in phrases, wrong addition of prepositions, wrong use of verbs, wrong use of phrasal verbs, wrong use of adjectives ending in –ed and –ing and redundant expressions. An analysis of the speech errors indicates that preposition was the most frequent type of grammatical error made by the learners. In addition, intralingual transfer was found to be the most prominent source of error. Key words: Error analysis Grammatical errors Interlingual errors Intralingual errors